Someone please help

Find all functions f:f:\Re \rightarrow \Re such that

f(x2+yf(z))=xf(x)+zf(y)f({ x }^{ 2 }+yf(z))=xf(x)+zf(y).

Please do post some suggestions on how to solve functional equations.

#Algebra #FunctionalEquations

Note by Priyanshu Mishra
5 years, 8 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

What have you tried? With functional equations, a lot of times it boils down to testing a bunch of values, and then being smart about choosing the variables.

What solutions have you found so far? That could guide you in thinking about the possible approaches.

Check out Functional Equations

Calvin Lin Staff - 5 years, 8 months ago

Let P(x,y,z)P(x,y,z) be the statement f(x2+yf(z))=xf(x)+zf(y)f(x^2+yf(z)) = xf(x)+zf(y).

First, f(x)=0f(x) = 0 for all xx is clearly a solution. For the rest of this solution, assume there exists cc such that f(c)0f(c) \neq 0.

ff is injective. To see this, suppose f(a)=f(b)f(a) = f(b). Then:

P(0,c,a)    f(cf(a))=af(c)P(0,c,a) \implies f(cf(a)) = af(c)

P(0,c,b)    f(cf(b))=bf(c)P(0,c,b) \implies f(cf(b)) = bf(c)

But f(a)=f(b)f(a) = f(b), so af(c)=f(cf(a))=f(cf(b))=bf(c)af(c) = f(cf(a)) = f(cf(b)) = bf(c), or af(c)=bf(c)af(c) = bf(c). Since f(c)0f(c) \neq 0, we have a=ba = b.

P(0,0,0)    f(0)=0P(0,0,0) \implies f(0) = 0

P(0,x,x)    f(xf(x))=xf(x)P(0,x,x) \implies f(xf(x)) = xf(x)

P(x,0,0)    f(x2)=xf(x)P(x,0,0) \implies f(x^2) = xf(x)

Thus f(x2)=xf(x)=f(xf(x))f(x^2) = xf(x) = f(xf(x)), or f(x2)=f(xf(x))f(x^2) = f(xf(x)). Since ff is injective, we have x2=xf(x)x^2 = xf(x). For nonzero xx this gives f(x)=xf(x) = x. Conveniently, when x=0x = 0 the same also applies, so we get the only other solution f(x)=xf(x) = x for all xx.


As you can see above, some functional equations are easily solved by simply substituting the right values. Occasionally, finding whether the function is injective/surjective also helps, especially when you have nested functions (function application inside function application). Sometimes you can also try ruling out the obvious answers so you can use a particular property (for example, say that all zero function works/doesn't work, so that for the rest of the problem you can assume there exists a nonzero value).

Ivan Koswara - 5 years, 8 months ago

Log in to reply

Thanks a lot.

Priyanshu Mishra - 5 years, 8 months ago

i think f(x)=x is the solution because first of all the it has to be an odd function ....that can be proved by putting -x in the place of x and subtracting both the eqns.....then....... replace x^2 +y f(z) with -ve of that ....on LHS rewrite -z f(y) as z f(-y).....and on RHS write -x^2 as x f(-x) and now compare...

Shanthan Kumar - 5 years, 7 months ago

Log in to reply

You have found 1 solution. How do you know that there are no other solutions?

For example, f(x)=0f(x) = 0 is another solution. How was that missed in your explanation?

Calvin Lin Staff - 5 years, 7 months ago

Log in to reply

Ohh...sorry i have cancelled that while solving....yea ...its the other solution... thanks for it btw... and u get that also when u replace x with -x and subtract..

Shanthan Kumar - 5 years, 7 months ago

Log in to reply

@Shanthan Kumar So, how do you know that there are no other solutions that you "cancelled" out?

Calvin Lin Staff - 5 years, 7 months ago
×

Problem Loading...

Note Loading...

Set Loading...